Strategic agility through improvisational capabilities - Cunha, Miguel Pina e (2020)
Organizations, especially, multinationals, inevitably confront contradictory challenges. One crucial challenge is the value of strategic consistency versus the value of rapid change related to unexpected problems, opportunities and fast moving trends. Accentuating the previously planned strategy can reduce temporal responsiveness; accentuating the immediate problems/opportunities can harm overall consistency. Strategic agility offers a potential path to resolve this paradoxical situation. In this article we advance a vision in which firms nourish improvisational capabilities in order to enhance strategic agility. We develop six HRM domains of action that can enhance effective improvisation and can inform the practice of a paradox-informed HRM. We discuss their implications for HRM-based strategic agility, paradoxical HR, and improvisation.